C.1 - Maharishi, Anuradha (Ed.) (New Delhi, 2002)
A Common Cause brings on to a single platform views from varied quarters on the role of the voluntary sector and concerns for its future. Grassroots workers, leaders of movements, founders of NGOs, programme managers of funding agencies, keen observers from the state, and intellectuals share their observations and reflections on diverse aspects of voluntary action. Institution building, ideological foundations, sources of motivation, relationships with the state and other stakeholders, histories of voluntarism, the importance of constructive work and the merit of movements these and other issues are debated and choices for the future are assessed. The essays reflect the urgent need to uncover and share the dilemmas and constraints of working towards egalitarian and democratic agendas.
Keywords: Civil society